Biomasa dan Cadangan Karbon Tanaman Berkayu di Hutan Desa Sungai Pelang, Kabupaten Ketapang, Kalimantan Barat - Khansa Falere Subarkah; Tatik Suhartati; Hastanto Bowo Woesono; Purwadi (Jurnal Wana Tropika, 2025)
The Sungai Pelang Village Forest, Block 11 Sub-block G, possesses a diversity of vegetation consisting of various species with different growth stages and has the potential to store carbon stocks. This research aims to estimate the biomass and carbon stocks of various woody plant species. The estimation uses a non-destructive method. The sampling method employed was the transect line method with a 10% sampling intensity, resulting in 13 observation plots with a distance of 63 meters between plots. The data collected included diameter, tree height, and the specific gravity of the species found. The results showed that the estimated total biomass is 87,40 tons/ha, and the carbon stock is 41,08 tons/ha, which is dominated by the tumih wood (Combretocarpus rotundatus (Miq.) Danser) and Geronggang (Cratoxylum arborescens).